Facile synthesis of copper selenides with different stoichiometric compositions and their thermoelectric performance at a low temperature range. Issue 42 (28th July 2021) - Li, Longbin; Zhao, Yifang; Shi, Chaosheng; Zeng, Wei; Liao, Bing; Zhang, Mingqiu; Tao, Xiaoming
Abstract : Copper selenides with different stoichiometric compositions were prepared via facile wet-chemistry methods and sintered-Cu2− x Se exhibited the highest ZT value at a low temperature range. Abstract : Copper selenide is widely considered to be a promising candidate for high-performance flexible thermoelectrics; however, most of the reported ZT values of copper selenides are unsatisfactory at a relatively low temperature range. Herein, we utilized some wet chemical methods to synthesize a series of copper selenides. XRD, SEM and TEM characterizations revealed that CuSe, Cu3 Se2 and Cu2− x Se were prepared successfully and possessed different morphologies and sizes. Based on the analysis of their thermoelectric properties, Cu2− x Se exhibited the highest Seebeck coefficient and lowest thermal conductivity among the three samples owing to its unique crystal structure. After being sintered at 400 °C under N2 atmosphere, the electrical conductivity of Cu2− x Se enhanced considerable, resulting in a significant improvement of its ZT values from 0.096 to 0.458 at 30 to 150 °C. This result is remarkable for copper selenide-based thermoelectric materials at a relatively low temperature range, indicating its brilliant potential in the field of flexible thermoelectric devices.